Ethical use of information technology resources among student: A case study at Universiti Utara Malaysia (UUM) - Raja Idris, Raja Siti Nurhidayah; Sheik Osman, Wan Rozaini (2006)
Developing the computer ethics policy is really important in educate the better attitudes for all students.Previous researches and result from the survey shows there are unethical behaviors and incidences in UUM campus.Thus, this study examines student’s awareness of UUM ICT Policy. Result from the survey show that more than three quarters of respondents (83.9%) have no idea about ICT policy.This research will provide the information and behaviors about UUM student’s knowledge about computer ethic codes/ICT policy.The output from the research can be use to maximize the ICT facilities for learning and academic purposes. The final output of this study is an action plan that can be used for UUM computer centre (UUMCC) to implement the Computer Ethics Codes.